Eliminating premature end peeling of flexurally strengthened reinforced concrete beams - Alam, M.A.; Jumaat, Mohd Zamin (Journal of Applied Sciences, 2009)
This study presents the results of an experimental study investigating the effect of U-shaped end anchors on flexurally strengthened reinforced concrete beams for the prevention of premature end peeling. A simple design guideline for the anchorage length of end anchor is proposed. A total of five beams, each 2300 mm long, 125 mm wide and 250 mm deep with a tension steel reinforcement ratio of 0.73, was cast and tested. One beam was left un-strengthened and used as a control, two beams were strengthened with steel plates and the remaining two beams were strengthened with Carbon Fibre Reinforced Polymer (CFRP) laminates. One each of the steel plate and CFRP laminate strengthened beams were further strengthened with mild steel U-shape end-anchors at both ends of the beams. The beams were then tested under two-point loading. The experimental results revealed that the U-shaped end anchors of designed anchorage length eliminated premature end peeling and it had significant effects on the failure mode, ultimate load, deflections and strain characteristics of the strengthened beams. It is seen from the results that the end-anchored strengthened beams showed higher ultimate load and more ductile behaviour compared to the un-anchored strengthened beams.